A review on CO2 leakage detection in shallow subsurface using geophysical surveys. (November 2020) - Caesary, Desy; Song, Seo Young; Yu, Huieun; Kim, Bitnarae; Nam, Myung Jin
Highlights: Effects of leaked CO2 on shallow-subsurface geophysical properties are detectable to geophysical measurements. Geophysical measurements to detect injected CO2 in laboratories and test bed fields were analyzed to discuss the merits and limitations of each geophysical method. Geophysical surveys made in CO2 injection fields as well as natural CO2 gas vents were able to detect CO2 leakage in the shallow subsurface. Abstract: Carbon capture and storage via the injection of carbon dioxide (CO2 ) into deep saline aquifers, also known as geological storage of CO2, has been used to mitigate greenhouse gas emissions. However, geologically sequestered CO2 can seep out through leaky wells and faults, thereby contaminating groundwater and reaching the atmosphere. Several facilities for controlled injection of CO2 into the shallow subsurface have been constructed to enhance understanding of the impacts of CO2 on the physical properties of the subsurface and to improve the early detection of CO2 leakage, before it reaches the atmosphere. Among various monitoring methods, geophysical methods have been employed widely to detect CO2 plume migration at shallow depths before CO2 enters the atmosphere. In this study, geophysical monitoring during CO2 injection at eight field sites and in five laboratory experiments was reviewed and analyzed. The analysis encompassed not only changes in subsurface geophysical properties, such as bulk electrical resistivity, complex resistivity, induced-polarization parameters, and electrical permittivity related to the presence of CO2, but also the effects of geological conditions on changes in these geophysical properties. Case studies of geophysical monitoring for natural CO2 leakage from gas vents are also discussed to provide real examples of CO2 degassing and leakage into the atmosphere. Geophysical surveys are sufficiently effective and sensitive for the monitoring of changes in geophysical properties due to the presence of CO2 leaked from sequestration reservoirs, and will be much more effective after the identification of high-risk regions for CO2 leakage from the Earth's surface.